Water availability in a university campus: the role of an artificial lake as a nature-based solution - Merchán-Sanmartín, Bethy; Arteaga-Bravo, Itati; Suárez-Zamora, Sebastián; Velásquez-Molina, Ana; Rosales-Serrano, Pablo; Arias-Hidalgo, Mijail; Jaya-Montalvo, María; Aguilar-Aguilar, Maribel; Carrión-Mero, Paúl (Frontiers in Water, 2025)
IntroductionEscuela Superior Politécnica del Litoral (ESPOL) is a Higher Education Institution (HEI) located in a protected tropical dry forest that uses Nature-Based Solutions (NbS) (albarradas and artificial lakes) for water resource management and ecosystem conservation. This research aims to evaluate the water availability of an artificial lake at ESPOL through the water balance, focused on two consumption scenarios for the total or partial water provision to the campus community.MethodsThe study included: (i) water availability assessment; (ii) criteria operationalization using the Analytical Hierarchy Process (AHP) and the Likert scale for the location of the Drinking Water Treatment Plant (DWTP); and (iii) analysis of Strengths, Weaknesses, Opportunities, and Threats (SWOT) for sustainable management strategies.ResultsThe lake can supply the ESPOL campus’s water needs without a deficit until 2041. However, considering technical and environmental aspects, its use could be extended until 2055. Water quality tests indicate that ESPOL Lake represents an acceptable source for the proposed purposes, provided it receives adequate treatment. Furthermore, the campus has an elevated reservoir located in a high area, whose adjacent areas offer better conditions for implementing a drinking water treatment plant. Finally, the proposed strategies for the sustainable management of the lake focused on optimizing water use, enhancing water infrastructure, and promoting academic engagement.DiscussionThis research supports the concept of living and dynamic laboratories in higher education institutions through the application of NBS as necessary sustainable practices in response to global warming.